2017
DOI: 10.1016/j.bbi.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Non-tumor cell IDO1 predominantly contributes to enzyme activity and response to CTLA-4/PD-L1 inhibition in mouse glioblastoma

Abstract: Glioblastoma (GBM) is the most common malignant brain tumor in adults with a median survival of 14.6 months. A contributing factor to GBM aggressiveness is the intratumoral expression of the potently immunosuppresive enzyme, indoleamine 2,3 dioxygenase 1 (IDO1). The enzymatic activity of IDO1 is associated with the conversion of tryptophan into downstream kynurenine (Kyn), which has previously been hypothesized to contribute toward the suppression of tumor immunity. Utilizing the syngeneic, immunocompetent, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…4D, E, F, G). This finding aligns with our previous observations in syngeneic, immunocompetent, intracranial mouse GBM models which showed that: (i) tumor cell IDO1 facilitates local Treg accumulation; (ii) Tc and Treg coincidently infiltrate IDO1-expressing tumors; and (iii) tumor cell IDO1 expression decreases animal subject survival (13, 36). Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…4D, E, F, G). This finding aligns with our previous observations in syngeneic, immunocompetent, intracranial mouse GBM models which showed that: (i) tumor cell IDO1 facilitates local Treg accumulation; (ii) Tc and Treg coincidently infiltrate IDO1-expressing tumors; and (iii) tumor cell IDO1 expression decreases animal subject survival (13, 36). Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, these outcomes were independent of the IDO1 effects on the Trp and Kyn levels mediated by tumor cells. 63 Instead, the majority of IDO1 metabolism was mediated by non-tumor cells of the engrafted intracranial glioblastoma. Also, IDO1 metabolism did not decrease the endogenous Trp levels within the brain tumor compared to a naive mouse brain without tumor cells.…”
Section: Novel Aspects Of Ido1 In Cancer Immunitymentioning
confidence: 99%
“…5,6 There are, however, notable exceptions to the general belief that more is better, and several recent studies have highlighted the fact that multi-therapy approaches do not universally provide an advantage to the host and/or immune system. 7,8 These considerations reflect the complicated regulatory network that governs the human immune system's response to cancer, its failure to have a 'one-size-fits-all' approach, the toxicities induced by certain immunotherapeutic combinations and the critical need to further understand why checkpoint therapies (i) provide benefits to some patients, but not others; (ii) enhance tumoricidal effects against some cancers, but not others; and (iii) beneficially stimulate immune responses with certain combinations, but not others.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nontumor-derived IDO1 possesses most of the Trp catabolic activity in mice injected with GL261. This analysis incorporated cervical lymph nodes in WT and IDO1-knockout mice, implicating peripheral IDO1 in modulating the antitumor immune response (26). Our finding that low IDO1 levels in peripheral blood before vaccination (week 0) were strongly correlated with longer PFS in our cohort suggests that SD patients may benefit from additional checkpoint blockade approaches, such as IDO inhibitors.…”
Section: Discussionmentioning
confidence: 86%